2013
DOI: 10.1371/journal.pone.0053579
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Stalk Interruption Syndrome in Chinese People: Clinical Characteristic Analysis of 55 Cases

Abstract: ObjectivePituitary stalk interruption syndrome (PSIS) is characterized by the absence of pituitary stalk, pituitary hypoplasia, and ectopic posterior pituitary. Due to the rarity of PSIS, clinical data are limited, especially in Chinese people. Herein, we analyzed the clinical characteristics of patients diagnosed with PSIS from our center over 10 years.Patients and MethodsWe retrospectively analyzed the clinical manifestations and laboratory and MRI findings in 55 patients with PSIS.ResultsOf the 55 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 24 publications
5
45
3
7
Order By: Relevance
“…This could be partly explained by the disparity in the ages and recruitment, although varied capacity of reestablishment of portal blood supply to the anterior pituitary might be a better explanation, yet it was impossible to be verified based on our data. Similar to another study of Chinese population, we observed a considerable variation in height. Even in the 27 patients without any treatment history, the height in one‐third of them might almost be considered normal or even in several cases relatively tall despite their uniformity of severe GH deficiency.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This could be partly explained by the disparity in the ages and recruitment, although varied capacity of reestablishment of portal blood supply to the anterior pituitary might be a better explanation, yet it was impossible to be verified based on our data. Similar to another study of Chinese population, we observed a considerable variation in height. Even in the 27 patients without any treatment history, the height in one‐third of them might almost be considered normal or even in several cases relatively tall despite their uniformity of severe GH deficiency.…”
Section: Discussionsupporting
confidence: 90%
“…In our study involving 74 adult patients, the age at diagnosis was 25 (22–28) years, significantly older than 3·6 years by Gascoin‐Lachambre et al., 4·0 years by Pinto et al . and 19·7 years by Guo et al., which made our population different than previously reported. We assumed atypical onset symptoms, negligence of short stature at early ages and insufficient understanding of the disease might attribute to this phenomenon to some extent.…”
Section: Discussioncontrasting
confidence: 72%
“… reported three patients with PSIS who had a single central incisor. However, not all of these features were observed in Han Chinese patients with PSIS . We retrospectively reviewed 112 sporadic cases examined in the past 10 years and only observed sparse hair and single central incisor in our patients.…”
Section: Clinical Findingsmentioning
confidence: 87%
“…The posterior pituitary function has been shown to be normal in these patients (1). A study of 55 patients with PSIS revealed documented breech delivery in 88.9% of the patients and the prevalence of deficiencies in growth hormone, gonadotropins, corticotropin, and thyrotropin were 100%, 95.8%, 81.8% and 76.3%, respectively (2). Timely diagnosis and replacement of the deficient hormones is the key to the management of these patients.…”
Section: Images In Endocrinologymentioning
confidence: 99%